Using ECHO as a decision support tool to manage coastal systems subject to physical changes. (5th June 2021) - Ahn, Jeong Eun; Ronan, Anne Dudek
Abstract: Physical changes in coastal systems, caused by human or natural processes, lead to changes in flow patterns and salinity, temperature and sediment distributions. These changes can affect the health of an ecosystem. This paper demonstrates the use of the model ECHO (coastal EC osystem H ealth assessment model using O ysters as the indicator species) for the assessment of the impacts on spatial distribution of the oyster zones. ECHO uses outputs of a 3-D hydrodynamic model to delineate zones hospitable to oysters; its outputs are much more concise than the extensive spatial and temporal outputs of the hydrodynamic models typically employed to simulate physical changes in a coastal environment. This study used ECHO to investigate the impacts of two hypothetical physical changes which altered hydrodynamics in a bay; the impacts were determined by examining the changes in the spatial extents of the delineated oyster zones. For the test cases, a region of a decreased water depth results in improved conditions for oysters, whereas adding an increased amount of freshwater inflow to the bay decreases the prevalence of oyster zones throughout the bay. ECHO reveals that the predominant reason for changes in the spatial extents of oyster zones in the latter case is prolonged stratification. By examining the spatial and temporal behavior of shear and density effects, we conclude that the Richardson number is a better means of quantifying stratification in a complicated tidal system than density gradients alone. Highlights: Demonstrate the use of ECHO as a predictive tool that can support decision-making for managing coastal systems. Investigate the impacts of two hypothetical physical changes which altered hydrodynamics in a bay. The impacts were determined by examining the changes in the spatial extents of the delineated oyster zone.